2017
DOI: 10.1515/jomb-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

The Monitoring of Protein Markers of Inflammation and Serum Lipid Concentration in Obese Subjects with Metabolic Syndrome

Abstract: SummaryBackgroundObesity is one of the most common modern health problems worldwide. Proinflammatory cells accumulate in the adipose tissue of the obese, and the presence of a low level chronic inflammation in obesity is associated with the emergence of a range of metabolic disorders in cluding cardiovascular disease, insulin resistance, type-2 diabetes, fatty-liver disease, and others. Neutrophils are early parti - cipants in inflammatory processes. After the appropriate stimu lation, these cells release reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
3
11
0
1
Order By: Relevance
“…Similar results were previously observed, showing that recurrent implantation failure patients with MetS (RIF-MS) decreased SOD and CAT levels in comparison with a control group, whereas the MPO levels increased in the MetS group [16]. Moreover, it has been also reported that MPO activity progressively increases with obesity and MetS [44].…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were previously observed, showing that recurrent implantation failure patients with MetS (RIF-MS) decreased SOD and CAT levels in comparison with a control group, whereas the MPO levels increased in the MetS group [16]. Moreover, it has been also reported that MPO activity progressively increases with obesity and MetS [44].…”
Section: Discussionsupporting
confidence: 87%
“…However, data on the incidence of metabolic syndrome (MetS) in persons infected with HIV vary considerably in various observational studies (9). MetS is a complex condition characterized by physical and metabolic abnormalities, which include central obesity, increased blood pressure, dyslipidemia and hyperglycemia (10).…”
Section: Introductionmentioning
confidence: 99%
“…The most common symptoms of vitamin B12 deficiency are hematological and/or neurological disorders (5, 6). Therefore, some risk factors of vitamin B12 deficiency have been investigated including lifestyle, age, and ethnic origin (7, 8, 9, 10, 11, 12, 13). Moreover, genetic predisposition was demonstrated in vitamin B12 deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, mutations and polymorphisms in transport proteins such as transcobalamin TCN, gastric intrinsic factor GIF and metabolic enzymes such as methylenetetrahydrofolate reductase MTHFR have been associated with vitamin B12 deficiency. Other vitamin-B12 related abnormalities like homocysteinemia and neural tube defect (NTD) have also been associated with genetic variants in these genes (13, 14, 15, 16, 17, 18, 19, 20, 21, 22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation